Pengaruh Bauran Pemasaran (Marketing Mix) Terhadap Kepuasan Konsumen Pada Usaha Jalangkote AZ (Studi Kasus di Desa Tukamasea Kecamatan Bantimurung Kabupaten Maros - Nur Aini; Mohammad Anwar Sadat; Azisah Azisah (Universitas Muslim Maros, 2022)
Jalangkote is one of the delicious foods originating from Makassar which is liked by many people from children to adults. In this study, the formulation of the problem is: Does the marketing mix affect consumer satisfaction in the Jalangkote AZ business in Tukamasea Village, Bantimurung District, Maros Regency. This research was conducted with the aim of knowing the effect of the marketing mix on consumer satisfaction in the Jalangkote AZ business in Tukamasea Village, Bantimurung District, Maros Regency. This study uses multiple linear regression analysis method to determine the effect of the marketing mix on consumer satisfaction in the Jalangkote AZ business in Tukamasea Village, Bantimurung District, Maros Regency. From the results of the study, it can be seen that consumer satisfaction in the Jalangkote AZ business in Tukamasea Village, Bantimurung District, Maros Regency which is influenced by the marketing mix is product and price.